2007
DOI: 10.1158/1055-9965.epi-07-0268
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Single-Nucleotide Polymorphisms in Colorectal Cancer and their Role as Modifiers of the Effect of Cigarette Smoking and Alcohol in the Singapore Chinese Health Study

Abstract: Recently, we reported that among Singapore Chinese, cigarette smoking and alcohol drinking were independent risk factors for colorectal cancer. Both tobacco smoking and alcohol use are plausible colorectal cancer risk factors, partly due to their ability to induce mutations in the colorectal lumen. . We conducted this study within the Singapore Chinese Health Study, a population-based cohort of 63,257 middle-aged and older Singapore Chinese men and women enrolled between 1993 and 1998. Our study included 1,176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 43 publications
9
57
2
Order By: Relevance
“…However, previous studies have reviled that Val762Ala SNP was associated with increased overall cancer risk only in Chinese population and was associated with decreased risk among Caucasians (Yu et al, 2012). In our study we found no significant association between PARP-1 Val762Ala SNP and risk of CRC in Saudi population, the same result was also found in Singapore Chinese population (Stern et al, 2007). Although PARP-1 Val762Ala SNP has been suggested to contribute in cancer development (Wang et al, 2007), to our knowledge, no previous studies have investigated the association between PARP-1 Val762Ala SNP and risk of CRC in Middle Eastern countries, particularly in Saudi Arabia.…”
Section: 3667 Characterization Of Novel Mutations Of the Parp-1 Genesupporting
confidence: 48%
See 2 more Smart Citations
“…However, previous studies have reviled that Val762Ala SNP was associated with increased overall cancer risk only in Chinese population and was associated with decreased risk among Caucasians (Yu et al, 2012). In our study we found no significant association between PARP-1 Val762Ala SNP and risk of CRC in Saudi population, the same result was also found in Singapore Chinese population (Stern et al, 2007). Although PARP-1 Val762Ala SNP has been suggested to contribute in cancer development (Wang et al, 2007), to our knowledge, no previous studies have investigated the association between PARP-1 Val762Ala SNP and risk of CRC in Middle Eastern countries, particularly in Saudi Arabia.…”
Section: 3667 Characterization Of Novel Mutations Of the Parp-1 Genesupporting
confidence: 48%
“…As we mentioned above this polymorphism was associated with increased risk of CRC only in Singapore Chinese population (Stern et al, 2007) and that was the only study done to associate between the PARP-1 Lys940Arg SNP and CRC susceptibility; therefore, it is unknown whether this SNP is or is not associated with CRC risk in other populations. Instead of Lys940Arg polymorphism, we found another alteration, with a heterozygous A/C allele, in 16% of the CRC patients and 12% of the control subjects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Associations between six single-nucleotide polymorphisms (SNPs) of the earlier-mentioned five genes and CRC have been reported in different ethnic groups (Smith et al, 2001;Landi et al, 2003Landi et al, , 2005Krzesniak et al, 2004;Jiang et al, 2005;McGreavey et al, 2005;Murtaugh et al, 2005;Slattery et al, 2005Slattery et al, , 2006Berndt et al, 2006;Huang et al, 2006;Koh et al, 2006;Kuriki et al, 2006;Matsuo et al, 2006;Moreno et al, 2006;Theodoropoulos et al, 2006;Tranah et al, 2006;Hansen et al, 2007;Kang et al, 2007;Stern et al, 2007;Vogel et al, 2007;Yin et al, 2007;Kury et al, 2008;Funke et al, 2009;Khatami et al, 2009;Tsilidis et al, 2009;Yang et al, 2009;Engin et al, 2010;Meplan et al, 2010;Loh et al, 2011;Wu et al, 2011;Crous-Bou et al, 2012;Gil et al, 2012). These six variants comprised rs12917 and rs2308321 of MGMT, rs1229984 of ADH1B, rs4880 of SOD2, rs2228001 of XPC, and rs1801282 of PPARG.…”
Section: Introductionmentioning
confidence: 99%
“…These coding polymorphisms, resulting in amino acid substitutions, were detected at codons 194 (Arg-Trp, rs1799782), 399 (Arg-Gln, rs25487) and 280 (Arg-His). Many authors have analysed relationship between the XRCC1 polymorphisms and the risk of several cancers, including colorectal cancer, however study findings have been inconsistent (Abdel-Rahman et al, 2000;Yeh et al, 2005;Stern et al, 2007;Jin et al, 2007Jin et al, , 2008Improta et al, 2008;Curtin et al, 2009;Wang et Canbay et al, 2011;Gsur et al, 2011;Reeves et al, 2012;Jelonek et al, 2012;Karahalil et al, 2012). Hong et al (2005) in South Korean and Yin et al (2012) in Japanese observed an increased risk of colorectal cancer associated with the XRCC1 Arg399Gln polymorphism and high alcohol intake.…”
Section: Introductionmentioning
confidence: 99%